Green Fluorescent Protein-mTalin Causes Defects in Actin Organization and Cell Expansion in Arabidopsis and Inhibits Actin Depolymerizing Factor's Actin Depolymerizing Activity in Vitro - Ketelaar, Tijs (American Society of Plant Biologists, 2004)
Expression of green fluorescent protein (GFP) linked to an actin binding domain is a commonly used method for live cell imaging of the actin cytoskeleton. One of these chimeric proteins is GFP-mTalin (GFP fused to the actin binding domain of mouse talin). Although it has been demonstrated that GFP-mTalin colocalizes with the actin cytoskeleton, its effect on actin dynamics and cell expansion has not been studied in detail. We created Arabidopsis (Arabidopsis thaliana) plants harboring alcohol inducible GFP-mTalin constructs to assess the effect of GFP-mTalin expression in vivo. We focused on the growing root hair as this is a model cell for studying cell expansion and root hair tip growth that requires a highly dynamic and polar actin cytoskeleton. We show that alcohol inducible expression of GFP-mTalin in root hairs causes severe defects in actin organization, resulting in either the termination of growth, cell death, and/or changes in cell shape. Fluorescence recovery after photobleaching experiments demonstrate that the interaction of GFP-mTalin and actin filaments is highly dynamic. To assess how GFP-mTalin affects actin dynamics we performed cosedimentation assays of GFP-mTalin with actin on its own or in the presence of the actin modulating protein, actin depolymerizing factor. We show that that GFP-mTalin does not affect actin polymerization but that it does inhibit the actin depolymerizing activity of actin depolymerizing factor. These observations demonstrate that GFP-mTalin can affect cell expansion, actin organization, and the interaction of actin binding proteins with actin.